Effect of okra mucilage addition on antioxidant properties of purple okra (Abelmoschus esculentus L. Moench) pudding - Jannah Miftahul; Damayanthi Evy; Nasution Zuraidah (BIO Web of Conferences)
Okra (Abelmoschus esculentus L. Moench) is a type of vegetable popular in various parts of the world. Okra has bioactive components such as flavonoids, polyphenols, and saponins that have the potential as antioxidants and anti-inflammatories [1]. Based on Utami (2018), purple okra has a higher phenol content and quercetin levels (2,034 ± 70.474 mg GAE 100 g-1 and 3,965 ± 0.449 mg 100 g-1) compared to green okra (1,807 ± 60.332 mg GAE 100 g-1 and 1,849 ± 0.449 mg 100 g-1) [2]. Not only okra pods, but okra mucilage is also proven to contain bioactive components that have health benefits for the human body. Bioactive compounds in purple okra mucilage, can be utilized in functional food. This study determined the effect of mucilage addition on the antioxidant properties of purple okra pudding. The addition of mucilage significantly (p<0.001) affected the antioxidant activity tested using the DPPH (2,2-diphenyl-1-picrylhydrazyl) method. Purple okra pudding with 20% mucilage has the highest antioxidant activity, which is 59.02% free radical inhibition that is equivalent with 24.95 mg vitamin C g-1 extract, and an IC50 value of 351.23. However, the addition of mucilage did not have a significant effect on total flavonoids and phenol content (p>0.05).